Electrodeposition of Pt - Rare Earth Alloys as ORR Catalysts for Fuel Cells. (30th August 2016) - Asen, Ludwig; Ju, Wenbo; Mostafa, Ehab; Martens, Sladjana; Heiz, Ueli; Stimming, Ulrich; Schneider, Oliver
Abstract : Electrochemical deposition was studied as a potentially scalable method for the preparation of Pt-rare earth alloys for application as cathode catalyst in proton exchange membrane fuel cells. For this purpose, experiments both on electrodeposition of platinum and of the rare earth elements yttrium and lanthanum were carried out in two different types of ionic liquid. While the electrodeposition of platinum was successful in both liquids, the deposition of the rare earth metals was more challenging. The deposition of Y in a TFSI based liquid was prevented by electrode passivation, while in a BF4 - liquid no passivation was seen, but also no clear indication of a deposition process was seen. For La, there was deposition using different precursors, but only at very low deposition rates. The nature of the deposit could not yet be unequivocally determined. Initial attempts in alloy deposition were not successful.